Monitoring fatigue and recovery in rugby league players - Twist, C.; Highton, J. (International Journal of Sports Physiology and Performance, 2013)
Rugby league is a contact team sport performed at an average intensity similar to that of other team sports (~70-80% VO2max), made up of unsystematic movements of varying type, duration, and frequency. The high number of collisions, repeated eccentric muscle contractions associated with accelerating and decelerating, and prolonged aerobic nature of rugby league matches result in the development of fatigue in the days after exercise. Monitoring the presence and magnitude of this fatigue to maximize performance and training adaptation is an important consideration for applied sports scientists. Several methods have been proposed to measure the magnitude of fatigue in athletes. Perceptual measures (eg, questionnaires) are easy to employ and are sensitive to changes in performance. However, the subjective nature of such measures should be considered. Blood biochemical markers of fatigue may provide a more objective measure of homeostatic disturbances associated with fatigue; however, the cost, level of expertise required, and high degree of variability of many of these measures often preclude them from being used in the applied setting. Accordingly, simple measure of muscle function (eg, jump height) and simulated performance offer the most practical and appropriate method of determining the extent of fatigue experienced by rugby league players. A meaningful change in each measure of fatigue for the monitoring of players can be easily determined, provided that the reliability of the measure is known. Multiplying the coefficient of variation by 0.3, 0.9, and 1.6 can be used to determine a small, moderate, and large change, respectively.